2023
DOI: 10.1186/s12866-023-03049-8
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial resistance profiles of salmonella spp. and escherichia coli isolated from fresh nile tilapia (oreochromis niloticus) fish marketed for human consumption

Millicent T. Mumbo,
Evans N. Nyaboga,
Johnson K. Kinyua
et al.

Abstract: Background Salmonella spp. and pathogenic strains of Escherichia coli are among the major foodborne zoonotic pathogens. These bacterial pathogens cause human illnesses characterized by hemorrhagic colitis, vomiting, nausea, and other agent-related symptoms. The increasing occurrence of antimicrobial resistance in these pathogens is also a serious public health concern globally. Regular surveillance of phenotypes and genotypes of Salmonella spp. and Escherichia coli from animal-derived foods is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 66 publications
0
1
0
Order By: Relevance
“…18 However, Mumbo et al reported that rifampicin resistance was observed in 11.1% of Salmonella isolates, and clinical efficacy was also observed in Salmonella Typhi and E. coli . 31 , 32 Furthermore, Salmonella was previously used as a model organism to investigate rifampicin resistance. 33–35 The wild-type Salmonella enterica exhibited MIC against rifampicin was 12 mg/L, whereas its rifampicin-resistant mutants showed high rifampicin resistance with MICs of 1500 to >3000 mg/L.…”
Section: Discussionmentioning
confidence: 99%
“…18 However, Mumbo et al reported that rifampicin resistance was observed in 11.1% of Salmonella isolates, and clinical efficacy was also observed in Salmonella Typhi and E. coli . 31 , 32 Furthermore, Salmonella was previously used as a model organism to investigate rifampicin resistance. 33–35 The wild-type Salmonella enterica exhibited MIC against rifampicin was 12 mg/L, whereas its rifampicin-resistant mutants showed high rifampicin resistance with MICs of 1500 to >3000 mg/L.…”
Section: Discussionmentioning
confidence: 99%
“…Salmonella spp. is not part of the healthy fish microbiota, and its presence indicates faecal contamination either from polluted water or cross-contamination during the production chain (unhygienic fish handling, fish processing, or marketing) [ 47 ]. Salmonella spp.…”
Section: Discussionmentioning
confidence: 99%